LEARNERS’ PERCEPTIONS OF THEIR WILLINGNESS TO COMMUNICATE IN ENGLISH IN DIFFERENT INTERACTIONAL CONTEXTS INSIDE THE CLASSROOM AT ILA: A CASE STUDY - Nguyễn, Hà Sâm (2020)
The fact that young learners at intermediate level at senior class at ILA, are not always active in learning has urged the need to investigate their willingness to participate in English inside the classroom. Looking at the matter from the students’ perspective, this paper seeks to detect their levels of willingness to communicate and find out the factors that influence the levels. By adopting methods of classroom observation, participant interviews and questionnaire, consistency between learners’ self-report WTC and their actual WTC behavior in the English classroom was examined. While trait-like WTC, as measured by a self-report survey, could predict a tendency to communicate, classroom observation of situational WTC and interviews with individual learners revealed actual behavior and the influence of contextual factors on the decision to engage in interaction with fellow students. A number of factors were perceived by learners to influence WTC behavior in class: self-confidence, background knowledge, group size, teacher support, format and content of the task given, familiarity with interlocutor, and interlocutor participation.